2018
DOI: 10.5535/arm.2018.42.4.521
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hand Training During the Aftereffect Period of Low-Frequency rTMS in Subacute Stroke Patients

Abstract: ObjectiveTo investigate the effects of hand training using low-frequency repetitive transcranial magnetic stimulation (rTMS) within the aftereffect period on hand function in patients with subacute stroke.MethodsThe subacute stroke patients with hand weaknesses were divided randomly into two groups. Patients in the intervention group underwent hand training within the aftereffect period, that is, immediately after receiving low-frequency rTMS treatment. Patients in the control group underwent hand training 2 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Thus, a higher ipsilesional excitability than the elevated ipsilesional excitability of the brain obtained through a single existing tool was induced. Second, the present study took advantage of the finding of a recent study which indicated that the second therapy of the combination therapy should be performed within 2 hours following the rTMS therapy to enhance the aftereffect and ultimately the efficacy of rTMS combined therapy by performing the robot therapy within 2 hours after the low-frequency rTMS therapy was completed [22]. Thus, the present study was conducted in a condition in which the increase in ipsilesional excitability of the brain and the suppression of the contralesional inter-hemisphere inhibition were maximized in comparison with other rTMS combined therapies targeting hemispatial neglect, through which the maximum treatment effect of the hemispatial neglect therapy was attempted to be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a higher ipsilesional excitability than the elevated ipsilesional excitability of the brain obtained through a single existing tool was induced. Second, the present study took advantage of the finding of a recent study which indicated that the second therapy of the combination therapy should be performed within 2 hours following the rTMS therapy to enhance the aftereffect and ultimately the efficacy of rTMS combined therapy by performing the robot therapy within 2 hours after the low-frequency rTMS therapy was completed [22]. Thus, the present study was conducted in a condition in which the increase in ipsilesional excitability of the brain and the suppression of the contralesional inter-hemisphere inhibition were maximized in comparison with other rTMS combined therapies targeting hemispatial neglect, through which the maximum treatment effect of the hemispatial neglect therapy was attempted to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the combined group were treated with both rTMS therapy and robot therapy. To maximize the therapeutic effect in the combined group, the rTMS therapy was performed first and then the robot therapy was performed within 2 hours after the first therapy was completed which was the aftereffect period [22].…”
Section: Methodsmentioning
confidence: 99%